Recent Advances of Oxidative Radical Cross‐Coupling Reactions: Direct α‐C(sp3)–H Bond Functionalization of Ethers and Alcohols - Guo, Sheng‐rong; Kumar, Pailla Santhosh; Yang, Minghua (Advanced synthesis & catalysis, 2017)
Oxygen‐containing heterocycles are an important class of compounds with diverse biological activities. In recent years, direct α‐C–H functionalization of inexpensive and abundant readily available ethers and alcohols by oxidative radical cross‐coupling with different nucleophilic partners (C–H, N–H, O–H and S–S), leading to the construction of C–C and C–X (X=C, N, O, S) bonds, has emerged as one of the vital strategies among oxidative cross‐coupling reactions. Owing to the features of being atom‐economic, environmentally benign, having a simple operation and biologically properties, a series of ether α‐C(sp3)–H bond activation reactions have been developed by metal or metal‐free systems via the radical oxidative coupling pathway, since the radical oxidative coupling reactions have wide range of applications. This review aims to highlight the recent advances in direct α‐C(sp3)–H bond functionalization of ethers and alcohols via radical oxidative process.